Pielęgniarka jako członek zespołu interdyscyplinarnego opiekującego się chorymi na raka jamy ustnej - Zrubáková, Katarína; Lehotska, Maria; Herinková, Anna; Podoba, Roman (Medical Studies/Studia Medyczne, 2020)
Anti-tumour treatment includes surgical, radiation, medication (chemotherapy, hormonal and biological treatment), supportive, and in some cases also palliative treatment. Chemotherapy and radiotherapy, or a combination of the two, involve the most clinical manifestations of adverse effects 1, 2. Adverse effects may be local or systematic and often they subside in the course of several weeks and months after the end of treatment [3, 4]. In the case of patients with unfavourable prognosis, the adverse effects continue for the rest of their life. One of the most frequently occurring complications is damage of oral mucosa [5, 6]. The oral cavity is not only endangered by radiotherapy (particularly with radiation in the area of head and neck) and chemotherapy, but it also suffers the consequences of neutropaenia and overall weakening of the body. The role of professionals is to use timely supportive and targeted treatment to reduce the damage and to attenuate the accompanying symptoms such as pain, dry mouth, xerostomia, oral infection, lack of appetite, swallowing disorders, and others.